Increased osteoblast function in vitro and in vivo through surface nanostructuring by ultrasonic shot peening - Guo Y (Dove Medical Press, 2015)
Yongyuan Guo,1,* Beibei Hu,2,* Chu Tang,1 Yunpeng Wu,1 Pengfei Sun,1 Xianlong Zhang,3 Yuhua Jia1 1Orthopaedic Department, 2Medical Examination Center, Qilu Hospital of Shandong University, Jinan, 3Orthopaedic Department, The Sixth Affiliated People’s Hospital, Medical School of Shanghai Jiao Tong University, Shanghai, People’s Republic of China *These authors contributed equally to this work Abstract: Surface topography has significant influence on good and fast osseointegration of biomedical implants. In this work, ultrasonic shot peening was conducted to modify titanium to produce nanograined (NG) surface. Its ability to induce new bone formation was evaluated using an in vivo animal model. We demonstrated that the NG surface enhanced osteoblast adhesion, proliferation, differentiation, and mineralization in in vitro experiments compared to coarse-grained titanium surface. Push-out test, histological observations, fluorescent labeling, and histomorphometrical analysis consistently indicated that the NG surfaces developed have the higher osseointegration than coarse-grained surfaces. Those results suggest that ultrasonic shot peening has the potential for future use as a surface modification method in biomedical application. Keywords: ultrasonic shot peening, titanium, in vivo, osseointegeration